An Improved Synthesis of 2-Aryl- and 2-Alkenyl-1,3,4-oxadiazoles by Using Copper(II) Oxide Nanoparticles as a Catalyst - Salva Reddy, N.; Raghavendar Reddy, P.; Das, Biswanath (Synthesis, 2015)
2-Aryl- and 2-alkenyl-1,3,4-oxadiazoles were efficiently synthesized in high yields by treatment of 1,3,4-oxadiazoles with aryl or alkenyl halides, respectively, in the presence of copper(II) oxide nanoparticles as a catalyst. The reusability of the catalyst is an important advantage in relation to practical applications of this synthesis.
Keywords: oxadiazoles; copper; catalysis; nanoparticles; arylations; alkenylations